UNDERSTANDING UNDIP INTERNATIONAL STUDENT'S EXPERIENCE IN THE ADAPTATION PROCESS OF INTERACTING TO THE HOST CULTURE - Dinaharilala Olivia, Randrianarison; Hasfi, Nurul; Rahardjo, Turnomo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The success of an international student is not only determined by his or her academic achievement but also by how well the student experiences the adaptation process by interacting with the host culture. Indonesia is one of the destination countries for foreign students to study, and for sure those students have to adapt to the new environment and interact with the local people by using the local language (Indonesian Language) and living with the host culture. However, how do Diponegoro University international students experience the adaptation process by interacting with the host culture in Semarang City? The purpose of this research is to describe the experience of International students when they adapt to the host culture, to analyze the experiences of international students by interacting with the host culture, and to describe the identity of international students after interacting with the host culture. The method used in this research is a phenomenology qualitative method by Max Van Manen (1990), with a deep interview with five international students from Rwanda, Sierra Leon, Madagascar, Pakistan, and Sudan. The result of this study highlights the adaptation process of international students interacting with the host culture which shows that the international students at Diponegoro University experience the same feeling upon arrival in the host culture which is excitement and surprise, also, all of them passed through the culture shock. The common shock was regarding the language, food, and social norms. However, to overcome the culture shock, each international student has their way of adapting, including, accepting the host culture, choosing not to interact with the host culture (not interact with the locals) and other was making a lifestyle change. In conclusion, it can be concluded that the culture shock was the cause of the challenge faced by those students, however, to adapt to the host culture, the 2 important is to make themselves comfortable, and the influence of the host culture, may change students' lifestyle.